2013
DOI: 10.1016/j.lwt.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Development of low-density polyethylene films with lemon aroma

Abstract: a b s t r a c tThe purpose of this study was to develop active films that impart flavour and to test them in the packaging of biscuits. The films were mechanically analysed, with respect to colour and water vapour permeability (WVP) to evaluate the changes in the films resulting from the active agents and conditioning time. We used low-density polyethylene with incorporated lemon essential oil (EO) and/or lemon aroma to create the films that were used in biscuits and evaluated over a 30 day period. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 20 publications
8
22
1
2
Order By: Relevance
“…have also demonstrated that the water vapor transfer process depends on the hydrophilic–hydrophobic ratio of the film constituents and hence the incorporation of hydrophobic oils in films decreases the WVTR and increases the barrier properties. According to Dias et al ., the presence of oil phase could increases the tortuosity factor in polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have also demonstrated that the water vapor transfer process depends on the hydrophilic–hydrophobic ratio of the film constituents and hence the incorporation of hydrophobic oils in films decreases the WVTR and increases the barrier properties. According to Dias et al ., the presence of oil phase could increases the tortuosity factor in polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
“…This also allows the combined application of natural antimicrobial agents and modified atmospheric packaging technologies to preserve quality and shelf life of fresh produce. Dias et al . developed low‐density PE (LDPE) based flavoring films with essential oils and lemon aroma for cereal products packaging.…”
Section: Introductionmentioning
confidence: 99%
“…Dias et al [48] also used EOs for developing a low-density polyethylene flavouring films imbued with and/or lemon aroma. They showed that the films had a lower elongation due to the incorporation of active agents, combined whit a reduction of tensile strength over time.…”
Section: Foodmentioning
confidence: 99%
“…This behavior was much pronounced for the films containing higher concentrations of the active mixture. Changes in the transparency of the films were also reported by Dias et al (2013) who found that extruded LDPE films with lemon aroma or lemon EO in the range of 5-10% showed a more opaque, yellow coloration and therefore less transparent with respect to films without active agents.…”
Section: Sealability Of Active Filmssupporting
confidence: 67%